(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
Phytochemical screening is an important step in detecting bioactive principles contained in therapeutic plants, and it might lead to the development of new therapeutics. The main phytoconstituents of chosen herbal plants were discovered in this study in order to link their presence to the bioactivities of the plants. The presence of steroids, alkaloids, flavonoids, carbohydrates, amino acids, and protein was detected using conventional techniques during the screening of the plants. The occurrence of these phytochemicals can be associated with a plant’s therapeutic potential. The collecting of plants, the extraction of active compounds from diverse sections of plants, and the qualitative and quantitative analysis of phytochemicals are the primary topics of this article. More research on these plants is needed to assess their pharmacological potentials, isolate, describe, and clarify the structures of the bioactive chemicals that are responsible for their actions, as well as additional medical applications.